PENGARUH CARBON EMISSION DISCLOSURE, ECO-EFFICIENCY DAN GREEN INNOVATION TERHADAP NILAI PERUSAHAAN ( STUDI KASUS PADA PERUSAHAAN INDUSTRY HIGH PROFILE TAHUN 2019-2023) - Febriani, Dwinda; Yuniarti, Rina (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to determine the influence of carbon emission disclosure, eco-efficiency, and green innovation on the value of high profile industry companies from 2019 to 2023. The population of this study has 241 companies. The sample of this study was selected using the purposive sampling technique, totaling 12 companies with an observation period of 5 years, so that the number of observation samples in the study was 60. The data analysis method used in this study is a quantitative method and uses panel data regression analysis techniques with the help of the Eviews 12 Software program. The results of the study show that carbon emission disclosure has an effect on the value of high profile industry companies in 2019-2023, eco-efficiency has no effect and is not significant on the value of high profile industry companies in 2019-2023 and green innovation has no effect and is not significant on the value of high profile industry companies in 2019-2023. Keywords: Carbon Emission Disclosure, Eco-Efficiency,Green Innovation, AND Company Value